IMPLEMENTASI GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KARYAWAN DI PT BPRS TULEN AMANAH - Ainul Arofah (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2024)
This study aims to find out how good corporate governance is implemented at PT BPRS Tulen Amanah, Masabagik District, and how good corporate governance plays a role in employee performance. The type of research used is descriptive qualitative research, with data collection techniques used, namely observation, documentation, and interviews. The data obtained is then analyzed using an inductive method that starts with a mindset then draws conclusions from specific data and then collects it to a more general level. The results of this study indicate that the implementation of the principles of good corporate governance, namely transparency, accountability, responsibility, fairness and independence have been implemented and juxtaposed with sharia principles. The implementation of good corporate governance has a composite title.